RANCANG BANGUN OPTIMASI SISTEM INFORMASI KOPERASI SIMPAN PINJAM BERBASIS WEB : (Studi Kasus : Koperasi Syariah Benteng Mikro Indonesia Cab. Curug Tangerang) - Abdurrahman Abdurrahman; Vivi Heryani (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2020)
This study aims to build a management information system for the Cooperative of Syariah Benteng Mikro Indonesia. Cooperative located in Kab. Tangerang is experiencing several obstacles in carrying out its transactions. So it is expected that an application can handle the problem. Such problems require a quick and precise solution with technology that is easy to operate and understood as a solution. With the programming language PHP (Personal Home Page) and MySQL will create a Web-based application. PHP is a script language that can be embedded or inserted into HTML. PHP can be used to build Web applications. MySQL is a SQL database management system or DBMS (Database Management System) software. With PHP and MySQL, Dynamic Duo will be a solution in building an information management system for goods and web-based transactions. With the web-based transaction application, it is able to overcome problems related to money management and transactions in the Koperasi Syariah Benteng Mikro Indonersia. Keywords: Cooperative Information Systems, Savings and Loans Cooperatives, Web Based, UML, Database